Letter from Campbell Morfit to James Curtis Booth, September 19, 1850 - Morfit, Campbell (1850)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Booth. Letter contains an early example of a "smiley face" in a message.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Emoticons